EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN GROUP INVESTIGATION (GI) PADA PEMBELAJARAN DIMENSI TIGA SISWA KELAS X SMA NEGERI SE-KABUPATEN WONOGIRI DITINJAU DARI TINGKAT KECERDASAN EMOSIONAL TAHUN PELAJARAN 2012/2013 - Tarmo Tarmo; Riyadi Riyadi; Imam Sujadi (Universitas Sebelas Maret, 2014)
Abstract: The objectives of this research were to investigate: (1) which one providing better learning achievement, the Jigsaw learning model, GI or direct instruction; 2) which one having better learning achievement, the students with high, medium or low emotional quotient (EQ); 3) in each category of EQ, which one providing better learning achievement, the Jigsaw, GI or direct instruction; 4) in each type of the learning model, which one having better learning achievement, the students with high, medium or low EQ. This research was a quasi-experimental research using factorial design of 3x3. The population of the research were all students of the Public Senior High Schools in Wonogiri Regency. The samples were chosen by using stratified cluster random sampling. The samples of the research were tenth grade students of SMA N 1 Wonogiri, SMA N 2 Wonogiri, and SMA N 1 Sidoharjo. In collecting the data, the instruments used were test and questionnaire. The technique of analyzing the data was unbalanced two-ways Anova. The results of the research are as follows: (1) the Jigsaw result in a better learning achievement than GI and direct instruction, the GI result in a better learning achievement than direct instruction; (2) the students with the high EQ result in a better learning achievement than the students with the medium or low EQ, the students with the medium EQ result in a better learning achievement than the students with the low EQ; (3) the students with the low EQ, the Jigsaw, GI and direct instruction have the same learning achievement; the students with the medium EQ, the Jigsaw and GI result in the same learning achievement, the GI learning model and direct instruction result in the same learning achievement and the Jigsaw result in a better learning achievement than direct instruction; the students with the high EQ the Jigsaw and GI result in the same learning achievement, and both result in a better learning achievement than the direct instruction; (4) in the Jigsaw and GI, the students with the low and medium EQ result in the same learning achievement, but students with the high EQ result in a better learning achievement than the students with the low or medium EQ, in the direct instruction, the students with the low, medium and high EQ result in the same learning achievement.Key words: learning model, Jigsaw, GI, emotional quotient.